Trigonometric Lengths

Geometry Level 3

In triangle A B C ABC , A C B = 9 0 \angle ACB = 90^\circ . Points A , D , E , A, D, E, and B B are consecutive points on side A B AB such that A D = D E = E B \overline{AD}=\overline{DE}=\overline{EB} . If there exists θ \theta such that C D = 5 cos θ \overline{CD} = 5 \cos \theta and C E = 5 sin θ \overline{CE} = 5 \sin \theta , what is A B 2 ? \overline{AB}^2?


The answer is 45.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

17 solutions

Rahul Nahata
May 20, 2014

Visit Brilliant's blog on Cosine Rule or Wikipedia - Apollonius's Theorem for more details and proof about Apollonius's Theorem.

Solution of the Problem:

Consider triangle D C B DCB ,
C E CE is a median.
Therefore, Applying Apollonius's Theorem on triangle D C B DCB
B C 2 + C D 2 = 2 ( D E 2 + C E 2 ) BC^{2} + CD^{2} = 2(DE^{2} + CE^{2})
Similarly in triangle A C E ACE ,
C D CD is a median.
Therefore, Applying Apollonius's Theorem on triangle A C E ACE
A C 2 + C E 2 = 2 ( D E 2 + C D 2 ) AC^{2} + CE^{2} = 2(DE^{2} + CD^{2})
Adding the above two relations yields,
B C 2 + C D 2 + A C 2 + C E 2 = 2 C E 2 + 4 D E 2 + 2 C D 2 BC^{2} + CD^{2} + AC^{2} + CE^{2} = 2CE^{2} + 4DE^{2} + 2CD^{2}
But A C 2 + B C 2 = A B 2 AC^{2} + BC^{2} = AB^{2} (Applying Pythagorean Theorem in triangle A B C ABC ). Using this relation and simplifying the above relation by cancelling common terms both the sides we get
A B 2 = C E 2 + C D 2 + 4 D E 2 AB^{2} = CE^{2} + CD^{2} + 4DE^{2}
Now as it is given that
C D = 5 cos θ CD = 5\cos\theta and C E = 5 sin θ CE = 5\sin\theta Our equation simplifies to
A B 2 = 25 sin 2 θ + 25 cos 2 θ + 4 D E 2 AB^{2} = 25\sin^{2}\theta + 25\cos^{2}\theta + 4DE^{2}
And as sin 2 θ + cos 2 θ = 1 \sin^{2}\theta + \cos^{2}\theta = 1
A B 2 = 25 + 4 D E 2 AB^{2} = 25 + 4DE^{2}
But we know D E = A B 3 DE = \frac{AB}{3} Therefore
A B 2 = 25 + 4 A B 2 9 AB^{2} = 25 + \frac{4AB^{2}}{9}
Hence
( 1 4 9 ) A B 2 = 25 (1 - \frac{4}{9})AB^{2} = 25
And this gives A B 2 = 45 AB^{2} = 45


WORLD CLASS SOLUTION. I AM SURPRISED TO USE SUCH TRICKS.

Priyanshu Mishra - 6 years, 5 months ago

This is cool!! But it is much easier to do it by coordinate geo. Work load reduced to half.! +1 bro

Rishabh Tiwari - 5 years ago

@Calvin Lin Is there a way to find theta?

Keshav Tiwari - 4 years, 11 months ago

Log in to reply

You could solve for it numerically, but what is the point of doing so?

Calvin Lin Staff - 4 years, 11 months ago

Log in to reply

Just like that. Do you mean by plugging in values for sides ?

Keshav Tiwari - 4 years, 11 months ago

Just wow!😍😍😍

arifin ikram - 1 year ago

First, we can draw 4 line segments from points D D and E E to side C B CB and A C AC such that these 4 segments are perpendicular to sides C B CB and A C AC . Since points D D and E E are evenly spaced on segment A B AB , we know that the perpendicular line segments drawn in must divide C B CB and A C AC each into 3 segments of equal length.

With these new segments, we have new right triangles. We now know that ( 2 3 C B ) 2 + ( 1 3 A C ) 2 = ( 5 sin θ ) 2 (\frac {2}{3}CB)^2 + (\frac {1}{3}AC)^2 = (5\sin \theta)^2 and ( 2 3 A C ) 2 + ( 1 3 C B ) 2 = ( 5 cos θ ) 2 (\frac {2}{3}AC)^2 + (\frac {1}{3}CB)^2 = (5\cos \theta) ^2 .

If we combine these two equations by adding them together, we get ( 2 3 C B ) 2 + ( 1 3 A C ) 2 + ( 2 3 A C ) 2 + ( 1 3 C B ) 2 = ( 5 sin θ ) 2 + ( 5 cos θ ) 2 (\frac {2}{3}CB)^2 + (\frac {1}{3}AC)^2 + (\frac {2}{3}AC)^2 + (\frac {1}{3}CB)^2 = (5\sin \theta)^2 + (5\cos \theta)^2 which can be simplified to 5 9 A C 2 + 5 9 C B 2 = 25 cos θ 2 + 25 sin θ 2 \frac {5}{9}AC^2 + \frac {5}{9}CB^2 = 25\cos \theta^2 + 25\sin \theta^2 .

We can then factor out the 25 from the right side of the equation. We know our trig identity which states that sin θ 2 + cos θ 2 = 1 \sin \theta^2 + \cos \theta^2 = 1 , so we can substitute it with one, leaving us with 5 9 A C 2 + 5 9 C B 2 = 25 \frac {5}{9}AC^2 + \frac {5}{9}CB^2 = 25 . After further simplification, we are left with the equation A C 2 AC^2 + B C 2 BC^2 = 45 .

In this equation, we are asked to find A B 2 AB^2 . Since it is a right triangle, we know that A C 2 AC^2 + B C 2 BC^2 = A B 2 AB^2 .

Therefore A B 2 = 45 AB^2 = 45 .

There were several ways to approach this problem. Apart from Pythagorean theorem and cosine rule, some other students favored Stewart's and Appollonius Theorem.

Calvin Lin Staff - 7 years ago
Rahul Sarathy
May 20, 2014

Drop the perpendiculars from D and E to BC, called F and G respectively.

Let α = D C F . \alpha = \angle DCF. Let β = C E G . \beta = \angle CEG.

Then D F = 1 3 A C = sin α 5 cos θ DF = \frac{1}{3}AC = \sin\alpha5\cos\theta C G = 1 3 B C = sin β 5 sin θ CG = \frac{1}{3}BC = \sin\beta5\sin\theta

1 9 A B 2 = 25 ( sin 2 α cos 2 θ + sin 2 β sin 2 θ ) \frac{1}{9}AB^2 = 25(\sin^2\alpha\cos^2\theta + \sin^2\beta\sin^2\theta)

C F = 2 3 B C = cos α 5 cos θ CF = \frac{2}{3}BC = \cos\alpha5\cos\theta G E = 2 3 A C = cos β 5 sin θ GE = \frac{2}{3}AC = \cos\beta5\sin\theta

4 9 A B 2 = 25 ( cos 2 α cos 2 θ + cos 2 β sin 2 θ \frac{4}{9}AB^2 = 25(\cos^2\alpha\cos^2\theta+\cos^2\beta\sin^2\theta

5 9 A B 2 = 25 ( sin 2 α cos 2 θ + sin 2 β sin 2 θ + cos 2 α cos 2 θ + cos 2 β sin 2 θ ) \frac{5}{9}AB^2 = 25(\sin^2\alpha\cos^2\theta + \sin^2\beta\sin^2\theta + \cos^2\alpha\cos^2\theta + \cos^2\beta\sin^2\theta)

= 25 ( cos 2 θ + sin 2 θ ) = 25 = 25(\cos^2\theta + \sin^2\theta) = 25 25 × 9 5 = 45 25 \times \frac{9}{5} = 45

Thomas Disy
May 20, 2014

Let C A B = α ∠CAB=\alpha and A B C = 90 α ∠ABC=90-\alpha we have that C D 2 = A C 2 + A D 2 2 A D A C cos α CD^2= AC^2 + AD^2 -2AD \cdot AC \cos\alpha and C E 2 = E B 2 + C B 2 2 E B C B cos ( 90 α ) CE^2=EB^2+CB^2-2EB\cdot CB \cos(90-\alpha) due to cosine rule. So we have C D 2 = A C 2 + D E 2 2 D E A C cos α CD^2= AC^2 + DE^2 -2DE \cdot AC \cos\alpha and C E 2 = D E 2 + C B 2 2 D E C B cos ( 90 α ) CE^2=DE^2+CB^2-2DE\cdot CB \cos(90-\alpha) since A D = D E = E B AD=DE=EB . We obtain C D 2 + C E 2 = A C 2 + C B 2 + 2 D E 2 2 D E ( A C cos α + C B cos ( 90 α ) ) CD^2+CE^2=AC^2+CB^2 +2DE^2 \\ -2DE(AC \cos\alpha+ CB \cos(90-\alpha))

by summing the equations above. Now we have that C D 2 + C E 2 = 25 ( ( cos θ ) 2 + ( sin θ ) 2 ) = 25 CD^2+CE^2=25((\cos\theta)^2+(\sin\theta)^2)=25 ( since ( cos θ ) 2 + ( sin θ ) 2 = 1 (\cos\theta)^2+(\sin\theta)^2=1 ). A C 2 + C B 2 = A B 2 = 9 D E 2 AC^2+CB^2=AB^2=9DE^2 (Pythagorean theorem) and A C cos α + C B cos ( 90 α ) = A B = 3 D E AC \cos\alpha+CB\cos(90-\alpha)=AB=3DE . So we have 25 = 9 D E 2 + 2 D E 2 2 D E ( 3 D E ) 25=9DE^2+2DE^2-2DE\cdot(3DE) and so 25 = 5 D E 2 25= 5DE^2 by substituting in the above equation. So D E 2 = 5 DE^2=5 and A B 2 = 9 D E 2 = 45 AB^2=9DE^2=45 .

Sai Krishna
May 20, 2014

In triangle AEC , CD is the median to AE. apply apollonius equation to it. similarly in triangle BCD, CE is the median to BD. apply apollonius equation to it. let AE=DE=BE=x and CD^2 +CE^2=25 and AC^2 +BC^2=9x^2. solve for x from the two equations.

Kevin Santer
May 20, 2014

We are told A D = D E = B E AD = DE = BE , therefore D and E must lie between A and B. For my explanation I will assume they lie in the order A D E B ADEB . If D and E are swapped, the results are the same. We can therefore deduce A E = 2 A D AE = 2AD and A B = 3 A D AB = 3AD .

We are told C D = 5 c o s θ CD = 5cos\theta and C E = 5 s i n θ CE = 5 sin\theta so C D 2 + C E 2 = 25 CD^2+CE^2 = 25 by the Pythagorean Identity

As A C B ACB is a right triangle, we know A C = A B c o s A = 3 A D c o s A AC = ABcosA = 3ADcosA

By the cosine rule:

C D 2 = A C 2 + A D 2 2 A C A D c o s A CD^2 = AC^2 + AD^2 - 2AC\cdot AD cosA C E 2 = A C 2 + A E 2 2 A C A E c o s A CE^2 = AC^2 + AE^2 - 2AC\cdot AE cosA

therefore C E 2 = A C 2 + 4 A D 2 4 A C A D c o s A CE^2 = AC^2 + 4AD^2 - 4AC \cdot AD cosA

By adding the first and third equations we get 25 = 2 A C 2 + 5 A D 2 6 A C A D c o s A 25 = 2AC^2 + 5AD^2 - 6AC \cdot AD cosA

so

25 = 2 ( 3 A D c o s A ) 2 + 5 A D 2 6 ( 3 A D c o s A ) A D c o s A 25 = 2(3ADcosA)^2 + 5AD^2 - 6(3ADcosA)ADcosA

25 = 18 A D 2 c o s 2 A + 5 A D 2 18 A D 2 c o s 2 A 25 = 18AD^2 cos^2 A + 5AD^2 - 18AD^2 cos^2 A

25 = 5 A D 2 25 = 5 AD^2

A D = ( 5 ) AD = \sqrt(5)

A B = 3 ( 5 ) AB = 3 \sqrt(5)

A B 2 = 45 AB^2 = 45

That's what I did

Ashish Sacheti - 5 years, 9 months ago
Ivan Stošić
May 20, 2014

Assume a coordinate system with the origin in the point C C and with points A = ( b , 0 ) A = (b,0) and B = ( 0 , a ) B = (0,a) for some arbitrary a a and b b .

The length of the hypotenuse A B AB is then equal to a 2 + b 2 \sqrt{a^2 + b^2} .

Since B E = E D = D A = 1 3 A C BE = ED = DA = \frac{1}{3} AC it is not hard to deduce the coordinates of points D D and E E . Think of a rectangle with corners in A A , B B and C C and divide it with a 3 by 3 grid.

Precisely, D = ( 2 3 b , 1 3 a ) D = (\frac{2}{3}b,\frac{1}{3}a) and E = ( 1 3 b , 2 3 a ) E = (\frac{1}{3}b,\frac{2}{3}a) .

We can then calculate C D CD and C E CE easily, since C C is the origin.

C D = 4 9 b 2 + 1 9 a 2 , C E = 1 9 b 2 + 4 9 a 2 CD = \sqrt{\frac{4}{9}b^2 + \frac{1}{9}a^2} , CE = \sqrt{\frac{1}{9}b^2 + \frac{4}{9}a^2}

We also have C D = 5 sin θ , C E = 5 cos θ CD = 5 \sin\theta , CE = 5 \cos\theta .

After we have eliminated C D CD and C E CE , squared both equations and added them together we have:

5 9 b 2 + 5 9 a 2 = 25 ( sin 2 θ + cos 2 θ ) \frac{5}{9}b^2 + \frac{5}{9}a^2 = 25(\sin^2 \theta + \cos^2 \theta)

Continuing on, we obtain:

5 9 b 2 + 5 9 a 2 = 25 \frac{5}{9}b^2 + \frac{5}{9}a^2 = 25

1 9 b 2 + 1 9 a 2 = 5 \frac{1}{9}b^2 + \frac{1}{9}a^2 = 5

b 2 + a 2 = 45 b^2 + a^2 = 45

Notice that A B 2 AB^2 is actually equal to b 2 + a 2 = 45 b^2 + a^2 = 45 , and so the solution is 45.

Zi Song Yeoh
May 20, 2014

By Stewart's Theorem applied to A C E \triangle ACE , and by the facts A E = 2 A D AE = 2AD and A B 2 = 9 A D 2 = A C 2 + B C 2 AB^{2} = 9AD^{2} = AC^{2} + BC^{2}

A D ( 25 s i n 2 θ + A C 2 ) = 2 A D ( 25 c o s 2 θ + A D 2 ) AD(25sin^{2}\theta + AC^{2}) = 2AD(25cos^{2}\theta + AD^{2}) 25 s i n 2 θ + A C 2 = 50 c o s 2 θ + 2 A D 2 \Rightarrow 25sin^{2}\theta + AC^{2} = 50cos^{2}\theta + 2AD^{2}

Similarly, applying Stewart's Theorem to C B D \triangle CBD , 25 c o s 2 θ + B C 2 = 50 s i n 2 θ + 2 A D 2 25cos^{2}\theta + BC^{2} = 50sin^{2}\theta + 2AD^{2} .

Adding the two equations, rearranging, and using s i n 2 θ + c o s 2 θ = 1 , A B 2 = 9 A D 2 = A C 2 + B C 2 sin^{2}\theta + cos^{2}\theta = 1, AB^{2} = 9AD^{2} = AC^{2} + BC^{2} ,

5 A D 2 = 25 A D 2 = 5 9 A D 2 = 45 A B 2 = 45 5AD^{2} = 25 \Rightarrow AD^{2} = 5 \Rightarrow 9AD^{2} = 45 \Rightarrow AB^{2} = 45 .

Brill Lent
May 20, 2014

Denote length of DE = x = AD = BE.

Apply Stewart's Theorem to triangle ACE and triangle BCD.

We have two equations:

xCE^2 + xAC^2 = 2x^3 + 2xCD^2 xCD^2 + xBC^2 = 2x^3 + 2xCE^2

Add the two equations. Also note that CD^2 + CE^2 = 25 and AC^2 + BC^2 = AB^2. Hence we get

25x + xAB^2 = 4x^3 + 50x AB^2 = 4x^2 + 25

AB^2 = (AD + DE + EB)^2 = (3x)^2 = 9x^2

9x^2 = 4x^2 + 25, therefore x^2 = 5. AB^2 = 9x^2 = 45.

By property of all right triangles, we will have (5\cos \theta)^2 + (5\sin\ theta)^2 = (5/9)(AB)^2 25\cos^2 \theta + 25\sin^2 \theta = (5/9)(AB)^2 25(\sin^2 \theta + \cos^2 \theta) = (5/9)(AB)^2 25(9/5) = (AB)^2 45 = (AB)^2

Devin Ky
May 20, 2014

Applying Stewart's Theorem, we get AC^2(BD) +BC^2(AD) = AB((BD)(AD)+CD^2) and AC^2(BE) +BC^2(AE) = AB((BE)(AE)+CE^2) since AD=DE=BE, we add both equations and express everything in terms of AD, we get AC^2(3AD)+ BC^2(3AD)=3AD(2AD^2+25(cos^theta +sin^2 theta)) using AC^2 + BC^2 = AB^2 and cos^theta +sin^2 theta = 1, after factoring 3AD we get AB^2 = 4AD^2+25, using the fact that AB = 3AD and solving the equation, we get AB^2 = 45.

Calvin Lin Staff
May 13, 2014

Applying Apollonius’ theorem ( Worked Example 3 ) to triangles A C E ACE and D C B DCB , we have

A C 2 + 25 sin 2 θ = 2 ( 25 cos 2 θ + 1 9 A B 2 ) , AC^2 + 25 \sin ^2 \theta = 2 \left(25 \cos^2 \theta + \frac {1}{9} AB^2\right), B C 2 + 25 cos 2 θ = 2 ( 25 sin 2 θ + 1 9 A B 2 ) . BC^2 + 25 \cos^2 \theta = 2 \left( 25 \sin^2 \theta + \frac {1}{9} AB^2 \right) .

Summing the 2 equations, we obtain A C 2 + B C 2 + 25 = 50 + 4 9 A B 2 AC^2 +BC^2+ 25 = 50 + \frac {4}{9} AB^2 . By the Pythagorean theorem, we have A C 2 + B C 2 = A B 2 AC^2 + BC^2= AB^2 , hence A B 2 = 25 × 9 5 = 45 AB^2 = 25 \times \frac {9}{5} = 45 .

Rab Gani
Dec 30, 2019

Draw straight lines through E and D parallel to BC, and through E and D parallel to AC, And let the distance form D to AC is x, and form E to BC is y. So we have AB^2 = 9 AD^2 = 9(x^2 +y^2). We have also CD^2 + CE^2 = 25, (x^2 +4 y^2) + (4 x^2 +y^2) = 25, or (x^2 +y^2)=5 . So AB^2 = 45

Steven Bateson
Mar 4, 2017

Rohit Sachdeva
Jun 22, 2016

In A C D \triangle ACD ,

c o s A = A C 2 + A D 2 C D 2 2 A C A D = A C A B cosA = \frac{AC^2 + AD^2 - CD^2}{2*AC*AD} = \frac{AC}{AB}

A C 2 + D E 2 25 c o s 2 θ 2 A C D E = A C 3 D E \frac{AC^2 + DE^2 - 25cos^2\theta}{2*AC*DE} = \frac{AC}{3DE}

A C 2 + D E 2 25 c o s 2 θ = 2 3 A C 2 \boxed{AC^2 + DE^2 - 25cos^2\theta = \frac{2}{3} AC^2}

In B C E \triangle BCE ,

c o s B = B C 2 + B E 2 C E 2 2 B C B E = B C A B cosB = \frac{BC^2 + BE^2 - CE^2}{2*BC*BE} = \frac{BC}{AB}

B C 2 + D E 2 25 s i n 2 θ 2 B C D E = B C 3 D E \frac{BC^2 + DE^2 - 25sin^2\theta}{2*BC*DE} = \frac{BC}{3DE}

B C 2 + D E 2 25 s i n 2 θ = 2 3 B C 2 \boxed{BC^2 + DE^2 - 25sin^2\theta = \frac{2}{3} BC^2}

Adding the 2 equations,

A B 2 + 2 D E 2 25 ( 1 ) = 2 3 A B 2 AB^2 + 2DE^2 - 25(1) = \frac{2}{3} AB^2

A B 2 + 2 ( A B 2 9 ) 2 3 A B 2 = 25 AB^2 + 2(\frac{AB^2}{9}) - \frac{2}{3} AB^2 = 25

A B 2 = 45 \boxed{AB^2 = 45}

Amed Lolo
Jan 30, 2016

in∆ cdb e is mid point of bd so ce is perpendicular to bd & CD=cb=5cos(theta). cos(cbd)=5cos(theta)\3be at∆ ABC. cos(cbd)=be\cos(theta),,cos^2(theta)\be^2=3\25. be=5cos(theta)\√3.at∆cbe cos(cbe)=5cos(theta)\√3÷5cos(theta) so. cos(cbe)=1\√3. So tan(cbe)=√2=5sin(theta)(5cos(theta)\√3). so tan(theta)=√2\√3. cos(theta)=√3\√5. So be=(5\√3)×(√3\√5)=√5. AB=3be=3√5 so AB^2=9×5=45########

Caleb He
May 20, 2014

We first may assume the angle is 45 degrees (since this is AIME), implying that CD=CE=5rt2/2. Now since CD=CE, it is implied that ABC is isosceles. Now we say AD=DE=EB=x. Therefore BC=3x/rt2. Apply law of cosines on CEB, we have (5rt2)^2=(3x/rt2)^2+x^2-2•(3x/rt2)•xcos45. Solving, we find x^2=5. We are looking for 9x^2, so our answer is 45.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...